Hermeneutika adil gender menurut ulama kontemporer dalam studi al-Qur’an - Muh. Hanif; Laila Nadzifatus Syarifah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
This article discusses the hermeneutical approach to gender in terms of comparisons from contemporary scholars. Islam is a religion that teaches justice or gender equality. However, the dominance of patriarchal ideology in the interpretation of the Qur'an results in a misogynistic interpretation that is not gender-just. Gender construction places the dominant male in the private sector, namely the family sphere, and the public sector, namely the community and work environment. Allah SWT judges His servants in terms of piety and faith, not from gender, ethnicity, nation, even descent. Contemporary scholars are trying so that the Qur'an can be understood its implied messages correctly and comprehensively, without taking sides with one group, class, more specifically on gender differences. The interpretation of Allah's messages from the Qur'an is sought to develop to be more gender-just. If the Qur'an is understood and interpreted textually only, it will result in a misogynistic interpretation of gender inequality that cannot solve the problems that develop. The implication is that the Qur'an is impressed as an outmoded product, a foreign product, perhaps even abandoned by its loyal followers. This view of gender as seen from hermeneutics has different perspectives but both uphold gender equality. The data sources used in this article are taken from various philosophical literature studies. The result is an equal position between women and men.